2018
DOI: 10.14311/gi.17.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Variation detection and respondents’ feedback: the cause, effect, and solution of oil spills.

Abstract: Abstract. Centred on occurrences of pipeline explosion and oil spills in a host community; a supervised classification technique, of land use/land cover variation detection was carried-out, with Landsat imageries of three time intervals, to determine the percentage of variation between the time intervals. Also carried-out, was a random sampling of questionnaires; dispatch to acquire respondents' feedback. It addressed respondents' demographic and social-economic composition of the sample population, the percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Therefore, there is a statistically significant difference in how long they have lived in the community and their educational background. Previous research findings (Makinde, 2014;Tologbonse, 2018) have shown that factors such as education and occupation influence the way respondents perceive certain environmental challenge confronting their communities.…”
Section: Questionnaire Resultsmentioning
confidence: 98%
“…Therefore, there is a statistically significant difference in how long they have lived in the community and their educational background. Previous research findings (Makinde, 2014;Tologbonse, 2018) have shown that factors such as education and occupation influence the way respondents perceive certain environmental challenge confronting their communities.…”
Section: Questionnaire Resultsmentioning
confidence: 98%